Mycobacterium tuberculosis Induction of Heme Oxygenase-1 Expression Is Dependent on Oxidative Stress and Reflects Treatment Outcomes - Rockwood, Neesha; Costa, Diego L.; Amaral, Eduardo P.; Du Bruyn, Elsa; Kubler, Andre; Gil-Santana, Leonardo; Fukutani, Kiyoshi F.; Scanga, Charles A.; Flynn, JoAnne L.; Jackson, Sharon H.; Wilkinson, Katalin A.; Bishai, William R.; et al. (Frontiers in Immunology, 2017)
The antioxidant enzyme heme oxygenase-1 (HO-1) is implicated in the pathogenesis of tuberculosis (TB) and has been proposed as a biomarker of active disease. Nevertheless, the mechanisms by which Mycobacterium tuberculosis induces HO-1 as well as how its expression is affected by HIV-1 co-infection and successful anti-tubercular therapy (ATT) are poorly understood. We found that HO-1 expression is markedly increased in rabbits, mice and non-human primates during experimental M. tuberculosis infection and gradually decreased during ATT. In addition, we examined circulating concentrations of HO-1 in a cohort of 130 HIV-1 co-infected and uninfected pulmonary TB patients undergoing ATT to investigate changes in expression of this biomarker in relation to HIV-1 status, radiological disease severity, and treatment outcome. We found that plasma levels of HO-1 were elevated in untreated HIV-1 co-infected TB patients and correlated positively with HIV-1 viral load and negatively with CD4+ T cell count. In both HIV-1 co-infected and M. tuberculosis monoinfected patients, HO-1 levels were substantially reduced during successful TB treatment but not in those who experienced treatment failure or subsequently relapsed. To further delineate the molecular mechanisms involved in induction of HO-1 by M. tuberculosis, we performed a series of in vitro experiments using mouse and human macrophages. We found that M. tuberculosis induced HO-1 expression requires NADPH-oxidase dependent reactive oxygen species (ROS) production induced by the early-secreted antigen ESAT-6 which in turn triggers nuclear translocation of the transcription factor NRF-2. These observations provide further insight into the utility of HO-1 as a biomarker of both disease and successful therapy in TB monoinfected and HIV-TB coinfected patients and reveal a previously undocumented pathway linking expression of the enzyme with oxidative stress.